Methods in econophysics: Estimating the probability density and volatility - Alghalith, Moawia (Frontiers in Physics, 2022)
We discuss and analyze some recent literature that introduced pioneering methods in econophysics. In doing so, we review recent methods of estimating the volatility, volatility of volatility, and probability densities. These methods will have useful applications in econophysics and finance.